1982
DOI: 10.1111/j.1469-8749.1982.tb13650.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual, Kinaesthetic and Cross‐modal Judgements of Length by Normal and Clumsy Children

Abstract: SUMMARY The ability of normal and clumsy children to match the length of lines within and between the modalities of vision and kinaesthesis was studied. The clumsy children showed perceptual impairments, as indicated by their poor performance on the visual, kinaesthetic and cross‐modal judgements of length and also by their low scores on spatial subtests of the wise. Variations in motor skill correlated with performance on the visual perceptual measures, but not with performance on the kinaesthetic or cross‐mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
4

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(22 citation statements)
references
References 9 publications
1
16
1
4
Order By: Relevance
“…Traditionally, sensory processing is considered to be a feedforward mechanism with information flow from the unimodal to the polymodal area [69]. New evidence indicates that feedback is possible from the higher visual cortex area (i.e., posterior parietal cortex) to middle temporal visual area [70]. This feedback process bears functional significance in that it influences immediate multisensory interaction [69] as well as bi-directional adaptation [71] (i.e., A modality affects B modality and vice versa).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, sensory processing is considered to be a feedforward mechanism with information flow from the unimodal to the polymodal area [69]. New evidence indicates that feedback is possible from the higher visual cortex area (i.e., posterior parietal cortex) to middle temporal visual area [70]. This feedback process bears functional significance in that it influences immediate multisensory interaction [69] as well as bi-directional adaptation [71] (i.e., A modality affects B modality and vice versa).…”
Section: Discussionmentioning
confidence: 99%
“…A related finding is that the level of motor involvement of a task also affects performance. A meta-analysis of 50 studies on Developmental Coordination Disorder children by Wilson and McKenzie (1998) established that effect sizes were higher for studies that involved active movement (e.g., Hulme, Biggerstaff, Moran & McKinlay, 1982) than passive movement (e.g., Laszlo & Bairstow, 1983). Other studies have also demonstrated that an active condition of a motor test, rather than a passive one, significantly discriminates Developmental Coordination Disorder children from a control group (e.g,.…”
Section: Discussionmentioning
confidence: 99%
“…22 Epidemiologically, the statistical equivalence between DDS and dyspraxia, and its comorbidity with DDS, is noteworthy. [5][6][7][10][11][12]22 Dyspraxia is a disorder of praxis, the Greek word meaning doing, acting, and practice. Praxis includes both knowing what to do and how to do it-doing something with ease and without effort.…”
Section: Developmental Delay Syndrome Linked To Motor Impairmentsmentioning
confidence: 99%
“…2 It has been shown that motor discoordination, especially affecting the postural and ocular muscles, is a common comorbid condition associated with this spectrum of disorders. [3][4][5][6][7] At this time, DDSs are thought to have multifactorial etiologies. 3,4,[8][9][10][11] The epidemiologic prevalence of these disturbances has been estimated to be as high as 5% to 20% (depending on a conservative definition).…”
mentioning
confidence: 99%